2020
DOI: 10.1021/acs.joc.0c00931
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Thiosubstituted Benzoxazoles via Copper-Catalyzed Coupling of Thiols with 5-Iodotriazoles Serving as Diazo Surrogates

Abstract: An efficient cascade approach to thiosubstituted benzoxazoles has been developed. The transformation starts with in situ generation of a diazo compound via annulation-triggered electrocyclic opening of the 1,2,3-triazole ring. The subsequent Cucatalyzed trapping of diazo intermediates by various thiols affords the desired heterocycles in generally good yields of up to 91%. The protocol features very good functional group tolerance and is applicable to substrates with different electronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…The introduction of ketone ( 3aa , 56%) and ester ( 3ab , 59%) moieties also led to somewhat diminished but still acceptable yields. Unexpectedly, the presence of a nitro group gave unsatisfactory result and caused a most dramatic decrease in the yield of product 3ac down to 19%, although the corresponding iodotriazole 1g was previously successfully used as a diazo precursor in Cu-catalyzed transformations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of ketone ( 3aa , 56%) and ester ( 3ab , 59%) moieties also led to somewhat diminished but still acceptable yields. Unexpectedly, the presence of a nitro group gave unsatisfactory result and caused a most dramatic decrease in the yield of product 3ac down to 19%, although the corresponding iodotriazole 1g was previously successfully used as a diazo precursor in Cu-catalyzed transformations …”
Section: Resultsmentioning
confidence: 99%
“…As part of our ongoing studies on preparation and reactivity of triazoles, we have recently disclosed a new type of convenient diazo precursors (Scheme B) . Our approach includes base-mediated cyclization of 5-iodotriazoles 1 bearing a pendant phenol group, followed by annulation-triggered triazole ring opening and in situ generation of diazobenzoxazoles 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, because of their structural analogy with biologically relevant α‐thiolated carboxylic acids, [12] 2‐thiomethyl benzoxazoles are also attractive targets in organic synthesis. The stepwise method employing prior functionalized diazomethyl benzoxazoles and sulfur nucleophiles has been realized by Kotovshchikov and co‐workers [13] . In addition, Bhadra et al [14] have reported the copper‐catalyzed synthesis of 2‐thiomethyl benzoxazoles via the C−H sulfenylation of 2‐methylene benzoxazoles.…”
Section: Entry Base Temp (°C) Solvent Yield (%)[B]mentioning
confidence: 99%
“…The stepwise method employing prior functionalized diazomethyl benzoxazoles and sulfur nucleophiles has been realized by Kotovshchikov and co-workers. [13] In addition, Bhadra et al [14] have reported the copper-catalyzed synthesis of 2thiomethyl benzoxazoles via the CÀ H sulfenylation of 2-methylene benzoxazoles. However, to the best of our knowledge, no synthetic method based on the benzoxazole annulation with thiol-functionalized acyclic substrates has hitherto been available.…”
mentioning
confidence: 99%
“…There are a variety of pathways to make benzoxazole compounds. Recently, the innovation of new methodologies for the preparation of benzoxazoles via oxidation of catechols with primary amines has resulted in more economical and very efficient strategies. So far, two types of transition metals, including Cu , and Fe , as the catalyst, have been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%